Selective Regulatory Effects of Lactobacillus Plantarum Fermented Milk: Enhancing the Growth of Staphylococcus Epidermidis and Inhibiting Staphylococcus aureus and Escherichia coli - Sun, Yajuan; Wang, Ying; Ren, Zixia; Wang, Shasha; Ding, Yun; Liu, Nan; Yang, Cheng; Zhao, Bingtian (Cosmetics (Basel), 2025)
To address the limitation of traditional broad-spectrum antimicrobial agents in compromising skin microbiota homeostasis, this study developed Lactobacillus plantarum fermented milk (FM) as an innovative strategy for selectively regulating microbial communities to restore skin microbiota balance. FM was produced through protease hydrolysis in combination with L. plantarum fermentation. Selective antibacterial properties were evaluated via monoculture experiments (Escherichia coli, Staphylococcus aureus, and Staphylococcus epidermidis) and pathogen–commensal co-culture systems. It was found that FM can selectively inhibit pathogens (E. coli and S. aureus) and promote the growth of commensal bacteria (S. epidermidis) in monoculture, and can reduce the growth and competitiveness of E. coli and S. aureus while relatively increasing the colony count of S. epidermidis in the co-culture system. Metabolomic profiling was further performed to identify metabolic alterations induced by FM. It was found that FM can activate the pyruvate metabolic node, significantly enhancing the metabolic fluxes of lactic acid, citric acid, and short-chain fatty acids, which triggered the acid stress response of pathogenic bacteria while consuming a considerable amount of energy, attenuating their reproductive capacity without impacting the growth of commensal bacteria. Overall, FM showed selective antimicrobial activity against pathogens (E. coli, and S. aureus) and preservation of commensal S. epidermidis, offering a foundational reference for the development of postbiotics aimed at maintaining cutaneous microbial homeostasis.